2019
DOI: 10.1111/jdv.16100
|View full text |Cite
|
Sign up to set email alerts
|

Does sunscreen use comply with official recommendations? Results of a nationwide survey in Germany

Abstract: Background The use of sunscreen can reduce the risk of UV-induced skin lesions. Health authorities have provided recommendations for the correct use of sunscreen use: Sufficient amount of sunscreen should be applied at least 30 min before the sun exposure and should be reapplied every 2 h.Objective We aimed to research the practice of sunscreen use in a population-based and representative sample in Germany. Methods For this cross-sectional survey, 3000 German residents aged 14-45 years were surveyed in standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 34 publications
2
25
2
Order By: Relevance
“…Since sunscreen use was the most common protective measure in our sample, parents should also be certain that they and their children use it correctly. A previous study from our research group showed deficits in the sunscreen use in the adult population [33], which also can lead to the occurrence of sunburn. These aspects should also be focused in information materials for parents/guardians.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Since sunscreen use was the most common protective measure in our sample, parents should also be certain that they and their children use it correctly. A previous study from our research group showed deficits in the sunscreen use in the adult population [33], which also can lead to the occurrence of sunburn. These aspects should also be focused in information materials for parents/guardians.…”
Section: Discussionmentioning
confidence: 81%
“…Thus, our data does not provide information on whether sunscreen use was in line with recommendations (e.g., kind of product, SPF, timing of application). Our previous survey showed, however, that sunscreen use in adults often did not comply with recommendations regarding timing of (re-)application and amount of sunscreen applied to the skin [33]. Therefore, it is important to address these aspects of sunscreen use in future studies focusing on children.…”
Section: Limitationsmentioning
confidence: 99%
“…swimming, excess friction from clothing or sand). [54][55][56] However, some of this loss of effectiveness may be offset through the usage of higher SPF sunscreens may partially compensate for poor application technique and adherence. 57,58 Underutilization is often exacerbated by additional barriers including: increased application challenges, poor comprehension of the risk of extensive UVR exposure, belief that tan skin appeared healthier, belief that sunscreen was harmful to the skin, or belief that sunscreens negatively impacts systemic vitamin D levels.…”
Section: Adherence Among the General Public Tomentioning
confidence: 99%
“…The recommendation suggests using a broad‐spectrum sunscreen with a sun protection factor (SPF) of 30 or higher, and the amount applied should be 2 mg/cm 2 to achieve the labeled level of sun protection. 2 , 3 , 4 However, the range of sunscreen applied in a real‐life setting was reported to be only 0.39 to 0.79 mg/cm 2 . 5 , 6 …”
Section: Introductionmentioning
confidence: 99%